Pergeseran Tradisi Bagurau Lapiak di Payakumbuh: Tradisi Klasik ke Modern - Oktavia, Rina; Ediwar, Ediwar; Asril, Asril; Rasmida, Rasmida; Jufri, Jufri; Desmawardi, Desmawardi (Jurnal Ilmiah Global Education, 2024)
Bogurau lapiak was originally a saluang dendang performance held in a shop with a mat and has been around since the 1980s. The performance is performed by senior drummers with one saluang, two drummers, and one janang / arranger of the performance. Today, the lapiak joke has shifted. The most noticeable shift can be seen from the drummers who fill the show are generally backgrounded as solo singers. They lack the skills and repertoire of classical saluang songs. The songs that are widely presented in bagurau lapiak performances now are dangdut songs, minang pop and gamad songs. This situation made senior drummers, rangers and laceurers worry about the loss of classic saluang songs. The presence of the lapiak bagurau show players is caused by several factors, namely, 1) economic factors, 2) technological factors and 3) market taste factors. This study used qualitative research with descriptive analysis methods. Data collection is done by observation, interviews, and documentation.